Efficiency of different doses of mineral fertilizers for winter wheat - N. I. Mamsirov; A. A. Mnatsakanyan (Новые технологии)
The regulated use of various types of mineral fertilizers in crop production directly affects the size and harvest quality of field crops, in particular winter wheat, which makes high demands on the diet. Even the most fertile soils, like chernozems, can be depleted over the years, with their constant use for crops and intense anthropogenic impact. The article presents the issues of mineral nutrition of varieties of winter soft wheat in the soil and climatic conditions of the Republic of Adygea. In the course of the research, it has been found that a high level of increase in the yield of winter wheat grain when using various doses of mineral fertilizer can be ensured due to the formation of timely and friendly seedlings of the culture, an increase in the total tilling capacity – 576 pcs/m2 and the productive one – 313 pcs/m2, in the intensity of accumulation of dry biomass by plants – 328 g/100 plants, in the «full ripeness» phase, ear lengthening – 7,1 cm and an increase in the amount of grain in it – 29 pcs., an increase in the mass of 1000 grains – 45,0 and other quality indicators. On average, according to the experience, the maximum yield of winter wheat is formed due to the introduction of a dose of N90P90K60 mineral fertilizer, where it was 4,60 t /ha for Goryanka and 4,74 t /ha for Maykopchanka. According to the analysis of the grain (protein content, gluten) and flour quality (strength of flour, volumetric yield of bread) of the studied wheat varieties, higher indicators were obtained when using the dose of N90P90K60 mineral fertilizer. Despite the high yield on this option, from an economic point of view, the most effective one was the option with the introduction of N30P30K30 fertilizers. When comparing the most optimal options for the two varieties (application of a dose of N30P30K30 fertilizers), the production of the Maykopchanka variety was more efficient.